Koolhidrate en -mobilisasie in Malus domestica Borkh. - Stassen, P. J. C.(Pieter Jacobus Cornelius) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc. Agric.) -- Universiteit van Stellenbosch, 1973.